Pengaruh Brand Ambassador Dan Tagline “Gratis Ongkir” Shopee Terhadap Keputusan Pembelian - Efdison, Zefri; Efridozel, Rahul; Fitriya, Sri; Yadewani, Dorris; Harahap, Erni Febrina (Bussman Journal : Indonesian Journal of Business and Management, 2025)
In the modern era, society's dependence on technology, particularly the internet, has brought significant changes in lifestyle, including shopping behavior. E-commerce, as a form of electronic commerce, is rapidly evolving as a mechanism for exchanging goods and services over the internet. This study aims to measure the influence of brand ambassadors and the "Gratis Ongkir" (Free Shipping) tagline of Shopee on the purchasing decisions of STIE Sakti Alam Kerinci students. The research results indicate a relatively low impact of both factors, with a Coefficient of Determination value of 14.3%. Despite being low, this value provides an initial overview of the extent to which the model can explain variations in students' purchasing decisions. The analysis reveals that the partial influence of brand ambassadors on purchasing decisions is 0.41%, while the "Gratis Ongkir" tagline has an impact of 0.34%. Although these figures are relatively low, it is essential to note that low values do not necessarily reflect insignificance. The reduced impact could be influenced by complex factors and variables not measured in the study. The Coefficient of Determination value of 14.3% indicates that the constructed model can explain a small portion of the variation in purchasing decisions among STIE Sakti Alam Kerinci students